(untitled) - Spengler, Oswald (London, 1962)
The Decline of the West is mainly known for Spengler's striking insights on diverse subjects that are everywhere in the book. It is also enlightening in it's overall metaphor of organic growth and decline of cultures and civilizations (what the book is mainly known for, but not its only virtue). Also he is very enlightening in his ability to describe universal type - within various subjects - and bring many things into perspective... If you already know basic, universal world history to any extent then Spengler's book - more so, I think, than other famous philosophies of history (Augustine's City of God, Hegel's History lectures, etc...) - can hit like a revelation. It's one of those books, though, that many people learn alot from but find it hard to recommend or - if they're famous or have reputations (academic, etc.) to consider - talk about publicly because people get such different things out of it. This is not an acecdote about liberal or conservative, but I remember reading once that Henry Kissinger gave an edition of Decline of the West to Richard Nixon as a gift. As I was saying, because the book has such large stereotypes attached to it neither of those two very public men would want to talk about the book publicly, but it is read - and is a must read to some degree - by most everybody who is really interested in getting an understanding of history...a subject very central to overall understanding of almost everything...
Keywords: Civilization,Văn minh; History,Lịch sử